Potential of palatal rugae patterns and index fingerprint as forensic identification tools in the Deutro-Malay Subrace: cross-sectional study - Kancana, Sildha Pura; Shalihah, Desyani; Malinda, Yuti; Zakiawati, Dewi; Supian, Sudradjat; Oscandar, Fahmi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Palatine rugae and fingerprints have unique pattern for each individual and have been proven to be used to support forensic identification. The fingerprint identification process can be difficult if the postmortem data is damaged. Palatine rugae have stable and accurate postmortem data but antemortem data are not yet available. This study aimed to analyze the potential of palatine rugae pattern and fingerprints as a means of forensic identification. Methods: This research was conducted in a correlational analysis on 191 Deutro-malay sub races aged 18-25 years. Samples of index and Index finger fingerprints were taken using an FM200 sensor and Zsoft Attendance software. Palatine rugae prints were obtained using occlusal photographs from a 70D DSLR camera. The pattern of both shapes was analyzed using the ImageJ application. Results: The most common pattern of rugae and fingerprints is a combination of the pattern of the rugae palatine curve and the pattern of the loop fingerprint (C-L). Both have a distinctive characteristic of recurving ridges. The pattern of the palatine rugae curve (C) was (25.5%) and the pattern of the Loop print (L) was (51%) on the index finger. Based on statistical analysis, with an error rate of 5%, there was a significant relationship between the 1st right rugae and right index finger (p=0.0004), and right index finger (p=0.005), 2nd left rugae with right index finger (p=0.0092) and 1st right rugae with left index finger (p=0.033). Conclusion: There is a relationship between the pattern of the index and index finger fingerprints with the shape pattern of palatine rugae. These findings can be used as a reference for the development of forensic odontology identification techniques.Keywords: ImageJ, forensic odontology, fingerprints, palatine rugae.Potensi pola bentuk rugae palatina dan sidik jari telunjuk sebagai sarana identifikasi forensik pada sub ras Deutro Melayu: studi cross-sectionalABSTRAKPendahuluan: Rugae palatina dan sidik jari memiliki pola khas setiap individu dan terbukti bisa digunakan sebagai penunjang identifikasi forensik. Proses identifikasi sidik jari bisa sulit dilakukan apabila data postmortem rusak. Rugae palatina memiliki data postmortem yang stabil dan akurat namun belum tersedia data antemortem. Tujuan penelitian ini untuk menganalisis potensi pola bentuk rugae palatina dan sidik jari sebagai sarana identifikasi forensik. Metode: Jenis penelitian dilakukan secara analitis korelasional pada 191 orang subras Deutero Melayu berusia 18-25 tahun. Sampel sidik jari telunjuk diambil menggunakan alat sensor FM200 dan software Zsoft Attendance. Sidik rugae palatina diperoleh menggunakan foto oklusal dengan kamera DSLR 70D. Pola bentuk keduanya dianalisis menggunakan aplikasi ImageJ. Hasil: Pola bentuk rugae dan sidik jari terbanyak adalah kombinasi pola bentuk rugae palatina. Curve dan pola sidik jari Loop (C-L). Keduanya memiliki karakteristik khas berupa recurving ridge.  Pola bentuk rugae palatina Curve (C) (25,5%) dan pola bentuk sidik Loop (L) (47,5%) pada telunjuk (51%). Berdasarkan analisis statistik, dengan taraf kesalahan 5% terdapat hubungan yang signifikan antara rugae ke-1 kanan dan telunjuk kanan (p=0,0004), rugae ke-1 kiri dengan telunjuk kanan (p=0,005), rugae ke-2 kiri dengan telunjuk kanan (p=0,0092) serta rugae ke-1 kanan dengan telunjuk kiri (p=0,033). Simpulan: Terdapat hubungan antara pola bentuk sidik jari telunjuk dengan pola bentuk rugae palatina. Temuan ini dapat menjadi acuan pada pengembangan teknik identifikasi forensik odontologKata kunci: ImageJ, forensik odontologi, rugae palatina, sidik jari.